2000
DOI: 10.1080/713803695
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length Analysis of ADP‐Ribose Polymers Generated by Poly(ADP‐Ribose) Polymerase (PARP) as a Function of ß‐NAD and Enzyme Concentrations

Abstract: SummaryBireactant autopoly(ADP-ribosyl)ation of poly(ADP-ribose) polymerase (PARP) (EC 2.4.2.30) was carried out by using either increasing concentrations of¯-NAD + (donor substrate) at a xed protein concentration or increasing concentrations of PARP (acceptor substrate) at a xed¯-NAD + concentration. The [ 32 P]ADPribose polymers synthesized were chemically detached from PARP by alkaline hydrolysis of the monoester bond between the carboxylate moiety of Glu and the polymer. Nucleic acid -like polymers were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Without the constraints found in vivo , ADP-ribose polymers can be extended to enormous lengths in vitro (D’Amours et al, 1999; Mendoza-Alvarez et al, 2000). It is likely that the formation of such a network of polymers could impair binding to cognate DNA sites in vitro due to simple steric hindrance.…”
Section: Parp-1 As a Regulator Of Transcriptionmentioning
confidence: 99%
“…Without the constraints found in vivo , ADP-ribose polymers can be extended to enormous lengths in vitro (D’Amours et al, 1999; Mendoza-Alvarez et al, 2000). It is likely that the formation of such a network of polymers could impair binding to cognate DNA sites in vitro due to simple steric hindrance.…”
Section: Parp-1 As a Regulator Of Transcriptionmentioning
confidence: 99%
“…1). These polymers consist of up to 200 units of ADP-ribose and may branch every 20 to 50 monomers [810]. To date, only four ARTD members were found to accomplish the synthesis of PAR, namely the DNA-dependent ARTD1 and ARTD2 as well as the tankyrases ARTD5 and ARTD6 [23].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that enzyme-bound ADP-ribose chain lengths are determined by the concentration of bNAD in the protein-poly(ADP-ribosyl)ation assay, regardless of the protein concentration in the incubation mixture [25]. Therefore, we next proceeded to determine the influence of the bNAD concentration on the electrophoretic mobility poly(ADP-ribosyl)ated-(pol b).…”
mentioning
confidence: 99%
“…We accomplished this by high-resolution polyacrylamide gel electrophoresis [24]. Gel slices containing the radiolabeled bands corresponding to automodified PARP-1 as well as poly(ADP-ribosyl)ated-pol b were separately analyzed after the chemical release of ADP-ribose chains from protein in 0.1m KOH in the presence of EDTA [25]. Fig.…”
mentioning
confidence: 99%